Personalized neoantigen DC vaccine combined with camrelizumab following definitive therapy in locally advanced unresectable esophageal squamous cell carcinoma (CHANT-241): protocol for a randomized controlled trial - Chen, Yueyun; Zheng, Yue; Shi, Huashan; Yang, Wenjie; Xu, Heng; Li, Yang; Ding, Zhenyu (Frontiers in Immunology, 2026)
ImportanceLocally advanced, unresectable esophageal squamous cell carcinoma (ESCC) has a poor prognosis despite definitive chemoradiotherapy (CRT), and no standard maintenance therapy currently exists. Personalized vaccines targeting tumor neoantigens combined with immune checkpoint inhibitors may enhance antitumor immunity, potentially improving these patients’ outcomes.ObjectiveTo evaluate whether maintenance therapy with a personalized neoantigen dendritic cell vaccine (Neo-DCVac) combined with camrelizumab improves overall survival (OS) compared to camrelizumab alone in patients with unresectable locally advanced ESCC following definitive CRT.Design, setting, and participantsThe CHANT-241 trial is a randomized, open-label, single-center, phase 2 clinical trial enrolling 165 patients aged 18 to 80 years with histologically confirmed unresectable locally advanced ESCC. Eligible participants must have completed definitive chemoradiotherapy (CRT) and undergone radiologic assessment within 3 to 5 weeks demonstrating no evidence of disease progression. Prior immunotherapy is allowed. Additional inclusion criteria include the ability to provide fresh tumor tissue or archived pathology slides of sufficient quality. Patients are randomized in a 2:1 ratio to receive either combination therapy or camrelizumab alone.InterventionPatients in the experimental group receive Neo-DCVac (0.5–2 × 107 cells per dose, subcutaneously, following cyclophosphamide pretreatment), administered as 5 priming doses and 10 booster doses over a 12-month vaccination period, in combination with camrelizumab (200 mg intravenously every 4 weeks). Patients in the control arm receive camrelizumab alone at the same dose and schedule.Main outcomes and measuresThe primary endpoint is the 2-year OS rate. Secondary endpoints include OS, progression-free survival (PFS), treatment-related adverse events (TRAEs), and exploratory biomarker analyses, including tumor mutational burden (TMB), PD-L1 expression, and circulating tumor DNA (ctDNA).ResultsClinical outcomes are not yet available. Upon completion of enrollment and data analysis, the study findings will be disseminated through publication in a peer-reviewed journal.ConclusionsThe CHANT-241 trial is designed to evaluate whether the addition of Neo-DCVac to camrelizumab as maintenance therapy improves survival outcomes in patients with unresectable locally advanced ESCC. The findings aim to provide high-level evidence supporting a novel precision immunotherapy approach in this population.Clinical Trial RegistrationClinicalTrials.gov, identifier NCT06675201.